Velocity scaling in open-channel flows with sediment transport - Corapi, Pietro; Acaro Chacón, Ximena Carolina; Chuquimarca Jimenez, Luis Enrique (Tecnología y ciencias del agua, 2021)
Under uniform and non-uniform flow conditions, the most employed velocity scale in OCFs is the shear velocity. In non-uniform flow conditions withÂ sediment transport, the log-law velocity distribution could be absent, so it is not possible to apply the conventional methods to compute the shear velocity. This work aims to define a way to compute the best value of velocity scale in non-uniform flows with different sediment transport under the absence of the log-law velocity distribution. Laboratory tests were performed by using a PIV system to measure the time and space velocity vectors, the total shear stress profiles were computed through the momentum balance analysis and the co-spectrum of the velocity fluctuation to define different values of the velocity scale factor. To determine which of the different values gives the better scaling of the velocity profiles, a comparison of the non-dimensional velocity profiles was done by showing that the value at the crest level from a linear regression of the shear stress profile, obtained with the momentum balance analysis, is the best velocity scale value.